Changes in clinical and imaging variables during withdrawal of heart failure therapy in recovered dilated cardiomyopathy. (8th March 2022) - Halliday, Brian P.; Owen, Ruth; Gregson, John; Vazir, Ali; Wassall, Rebecca; Khalique, Zohya; Lota, Amrit S.; Tayal, Upasana; Hammersley, Daniel J.; Jones, Richard E.; Pennell, Dudley J.; Cowie, Martin R.; et al.
Abstract: Aims: This study aimed to profile the changes in non‐invasive clinical, biochemical, and imaging markers during withdrawal of therapy in patients with recovered dilated cardiomyopathy, providing insights into the pathophysiology of relapse. Methods and results: Clinical, biochemical, and imaging data from patients during phased withdrawal of therapy in the randomized or single‐arm cross‐over phases of TRED‐HF were profiled. Clinical variables were measured at each study visit and imaging variables were measured at baseline, 16 weeks, and 6 months. Amongst the 49 patients [35% women, mean age 53.6 years (standard deviation 11.6)] who withdrew therapy, 20 relapsed. Increases in mean heart rate [7.6 beats per minute (95% confidence interval, CI, 4.5, 10.7)], systolic blood pressure [6.6 mmHg (95% CI 2.7, 10.5)], and diastolic blood pressure [5.8 mmHg (95% CI 3.1, 8.5)] were observed within 4–8 weeks of starting to withdraw therapy. A rise in mean left ventricular (LV) mass [5.1 g/m 2 (95% CI 2.8, 7.3)] and LV end‐diastolic volume [3.9 mL/m 2 (95% CI 1.1, 6.7)] and a reduction in mean LV ejection fraction [−4.2 (95% CI −6.6, −1.8)] were seen by 16 weeks, the earliest imaging follow‐up. Plasma N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) fell immediately after withdrawing beta‐blockers and only tended to increase 6 months after beginning therapy withdrawal [mean change in log NT‐proBNP at 6 months: 0.2 (95% CI −0.1, 0.4)]. Conclusions: Changes in plasma NT‐proBNP are a late feature of relapse, often months after a reduction in LV function. A rise in heart rate and blood pressure is observed soon after withdrawing therapy in recovered dilated cardiomyopathy, typically accompanied or closely followed by early changes in LV structure and function.